2008
DOI: 10.1007/s10354-008-0619-7
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoide in der Medizin

Abstract: Cannabinoids have been known for many centuries because of their various effects in healthcare. They are primarily effective in reducing nausea, vomiting, pain, anorexia, spasticity and depression. Some other effects are known, all seem to be mediated by cannabinoid receptors in the central nervous system. In the past years, medical use has been proven in several studies. Today, the therapeutical use of cannabinoids in medicine is increasing, and access was made easier. Especially in pain-management and pallia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Subsequently it became clear that the effects of THC are due to the activation of endogenous cannabinoid receptors within a newly discovered endocannabinoid system (ECS) [4]. More recently, the ECS has been associated with an increasing number of functional pathways, both in the central and peripheral nervous systems and in peripheral organs, and the ECS has emerged as a target of pharmacotherapy [5][6][7][8][9][10]. Endocannabinoids naturally produced in the body, for example in stress situations, modulate the ECS system and affect inflammation and the sensation of pain [7,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently it became clear that the effects of THC are due to the activation of endogenous cannabinoid receptors within a newly discovered endocannabinoid system (ECS) [4]. More recently, the ECS has been associated with an increasing number of functional pathways, both in the central and peripheral nervous systems and in peripheral organs, and the ECS has emerged as a target of pharmacotherapy [5][6][7][8][9][10]. Endocannabinoids naturally produced in the body, for example in stress situations, modulate the ECS system and affect inflammation and the sensation of pain [7,11].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the ECS has been associated with an increasing number of functional pathways, both in the central and peripheral nervous systems and in peripheral organs, and the ECS has emerged as a target of pharmacotherapy [5][6][7][8][9][10]. Endocannabinoids naturally produced in the body, for example in stress situations, modulate the ECS system and affect inflammation and the sensation of pain [7,11]. In the 1970s, the effect of THC on pain was compared to that of codeine [12], and more recent studies showed that THC is equivalent to conventional analgesics [13].…”
Section: Introductionmentioning
confidence: 99%